2008
DOI: 10.1371/journal.ppat.0040018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trim5 Polymorphisms on the Clinical Course of HIV-1 Infection

Abstract: The antiviral factor tripartite interaction motif 5α (Trim5α) restricts a broad range of retroviruses in a species-specific manner. Although human Trim5α is unable to block HIV-1 infection in human cells, a modest inhibition of HIV-1 replication has been reported. Recently two polymorphisms in the Trim5 gene (H43Y and R136Q) were shown to affect the antiviral activity of Trim5α in vitro. In this study, participants of the Amsterdam Cohort studies were screened for polymorphisms at amino acid residue 43 and 136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 36 publications
5
105
3
2
Order By: Relevance
“…The discovery of extensive diversity in TRIM5 between primate species begged the question of whether the locus would be polymorphic within species as well, and whether naturally occurring variants differentially affect susceptibility to retroviral infection or disease progression. Thus far, reports of extensive within-species sampling for polymorphism in TRIM5 have been limited to humans (Sawyer et al 2006), most commonly in the context of HIV/AIDS cohorts (Goldschmidt et al 2006;Javanbakht et al 2006;Nakayama et al 2007;Speelmon et al 2006;van Manen et al 2008), and two species of Old World monkey ( Fig. 5; Newman et al 2005;Wilson et al 2008a).…”
Section: Trim5 Sequence Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of extensive diversity in TRIM5 between primate species begged the question of whether the locus would be polymorphic within species as well, and whether naturally occurring variants differentially affect susceptibility to retroviral infection or disease progression. Thus far, reports of extensive within-species sampling for polymorphism in TRIM5 have been limited to humans (Sawyer et al 2006), most commonly in the context of HIV/AIDS cohorts (Goldschmidt et al 2006;Javanbakht et al 2006;Nakayama et al 2007;Speelmon et al 2006;van Manen et al 2008), and two species of Old World monkey ( Fig. 5; Newman et al 2005;Wilson et al 2008a).…”
Section: Trim5 Sequence Evolutionmentioning
confidence: 99%
“…Of the common protein-altering SNPs, only one (H43Y) was found to modulate activity against retroviruses in vitro; in this case, the 43Y allele weakens TRIM5α restriction (Sawyer et al 2006). This study brought H43Y forward as a candidate SNP for differential susceptibility of certain human populations, and at least one study has reported an association between the 43Y/Y genotype and accelerated disease progression (van Manen et al 2008). It will be especially interesting to explore the effects of TRIM5 genotype in cohorts from Central and South America, where the 43Y…”
Section: Trim5 Sequence Evolutionmentioning
confidence: 99%
“…Studies examining this question have produced conflicting results thus far. Polymorphisms in the Trim5a gene [95] and different expression levels of APOBEC3G [96] are associated with greater control of infection. However, this result has not been confirmed by other studies [97,98], and the expression of IFN-induced restriction factors may also be driven by viral replication [99].…”
Section: Insights Into Immune Responses Conferring Spontaneous Contromentioning
confidence: 99%
“…future science group Expression differences and TRIM5 polymorphisms influence rates of HIV-1 acquisition and/or disease progression [16]. Moreover, TRIM5 in nonhuman primates also plays an important role in limiting transmission of SIVs and in controlling the outcome of infection with these viruses [17].…”
Section: Future Microbiology Part Ofmentioning
confidence: 99%